2020
DOI: 10.1186/s13063-019-4002-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Checklist-Based Box System Interventions (CBBSI) versus routine care on improving utilization of maternal health services in Northwest Ethiopia: study protocol for a cluster randomized controlled trial

Abstract: Background: Maternal mortality is still high in Ethiopia. Antenatal care, the use of skilled delivery and postnatal care are key maternal health care services that can significantly reduce maternal mortality. However, in low-and middle-income countries, including Ethiopia, utilization of these key services is limited, and preventive, promotive and curative services are not provided as per the recommendations. The aim of this study is to examine the effectiveness of checklist-based box system interventions on i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The trial protocol for this study was published [ 16 ] and the trial was retrospectively registered on ClinicalTrials.gov, with trial identifier NCT03891030 on March 26, 2019.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trial protocol for this study was published [ 16 ] and the trial was retrospectively registered on ClinicalTrials.gov, with trial identifier NCT03891030 on March 26, 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Timing of postnatal visits followed the a recommendation from WHO and the nationally implemented three visit model: within 2 days of delivery (PNC 1), within 7 days of delivery (PNC 2) and within 42 days of delivery (PNC 3). The published protocol of this study includes a detailed description of the intervention [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Through health education, health extension workers, in which the dropping mother belong, were able to sway her to return to service. The “health education scheduling box” aided health extension workers in prioritizing health education topics during this process [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare systems based on place of residence and employment status can make it difficult for migrants to access health services [18], although increased health service utilization (including medical, healthcare, and rehabilitation services) would likely reduce adverse health outcomes in vulnerable populations. One study in particular found that maternal health services significantly reduced mortality rates among pregnant women [19]. However, due to the restrictions of China's household registration system, the floating population has both low awareness [20] and poor utilization of health services, and subsequent lower vaccination rates compared to local populations [21].…”
Section: Introductionmentioning
confidence: 99%